Groundwater contamination susceptibility as a function of soil properties in the Brazilian Cerrado - Mingoti, Rafael; Spadotto, Claudio Aparecido; Campos Moraes, Diego Augusto de [UNESP] (Empresa Brasil Pesq Agropec, 2016)
The objective of this work was to present an index for the characterization of soil susceptibility to groundwater contamination, as well as to perform an exploratory study of the soils from the Brazilian Cerrado biome. The water retention time (RT) index was determined with mean values obtained from a filtering methodology, in databases of the following soil properties: depth of the horizons; granulometry; organic carbon content; bulk density and particle density; and moisture content at field capacity. The water table depth was estimated using the Hand model. Spatial distributions of input data and TR index results were obtained using a geographic information system software. Soils that offer low protection to groundwater contamination by organic chemicals are located in southeast and east-central regions of the state of Mato Grosso, in the western of the state of Bahia, in the south of Goias, and in the north of Mato Grosso do Sul, Brazil. The predominant soil classes in the more susceptible areas are Neossolos Quartzarenicos orticos (Entisols) and Latossolos Vermelhos distroficos (Oxisols).
Keywords: territorial management; land cover; soil pollution; water resources; ecosystem services; geographic information system